Estructura, caracterización y estado de conservación de los recursos florísticos en la zona alta del bosque protector Murocomba, año 2018. - Aguayo Guerrero, Cristhian Alexis (2019)
The present investigation was carried out with the objective of determining the structure, characterization and state of conservation in the upper zone of the "Murocomba Protective Forest", belonging to Valencia, canton Los Ríos province. Two sampling units were installed, considering only the area with native forest cover within the property. With the use of indicators of diameter, total height of the individuals, species, family, index of importance value (IVI) and value of importance of families (IVF), the floristic composition and structure of the vegetation was demonstrated. A total of 197 individuals belonging to 29 families, 40 species and 17 genera were registered, being the families Clusiaceae and Lauraceae the most important and Otoba glycycarpa, Bactris gasipaes and Eschweilera awaensis (Baker) the most abundant species. The index of importance value (IVI) indicated that the species Guarea sp. with 54,07% Otoba glycycarpa with 21,72% and Myrcianthes rhopaloides con 17,97 % . They are the most representative in the study area. The Shannon index is 2,84 , which indicates that the study area has a great diversity of species, and the similarity index among the sampling units does not exceed 28% of similar species. The largest diameter was recorded in class V, with the Guarea sp., which generated the largest volume, 22.94 m3. At the parcel level, the most abundant was the 2 m x 2 m, with 127 individuals; however, the 20 m x 20 m sampling unit recorded 51 individuals in total from both plots. The results obtained from the structures in the plots made indicate that the trees do not exceed 40 meters in height, however, most of the DAP exceed 7.5 cm, this indicates that there is heterogeneity between species of different strata and an adequate process of ecological succession. Keywords: Strata; Heterogeneity; ecological succession; Sample Units.